Implementing project-based learning to enhance creative thinking skills on water pollution topic - Y. Yamin; Anna Permanasari; Sri Redjeki; Wahyu Sopandi (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
The implementation of Project-based learning (PjBL) has been recognized as a recommended alternative learning to habituate students to solve their daily problems. This study aimed to describe students’ creative thinking skills (CTS) in water pollution topic using PjBL. The descriptive method was used in this study. The sample in this study were junior high school students in the Bandung City, Indonesia. The instruments used in this study were CTS test, peer assessment, and product creativity assessment rubric.  The data gained were analysed using descriptive statistics analysis in terms of mean and percentage. The results showed that the mean test score of students' CTS was 89% (excellent category). The achievement of peer assessment indicators was 87%, while the performance of product creativity indicators was 88%.  This study concluded that the implementation of PjBL in science learning could improve the CTS of junior high school students.